THE EFFECT OF SQUAT THRUST TRAINING ON THE FLEXIBILITY OF KARATE ATHLETES - Tiara, Diana; Destriana, Destriana; Victorian, Achmad Richard (Universitas Negeri Medan, 2023)
This study aims to determine the effect of squat thrust training on KKI Sumsel Karate Dojo athletes. The method used in this study, namely quasy experimentation, is a research method that does not use random assignments but uses existing groups. The research design used is the One Group Pretest-Posttest Design. This sample was taken using a total population sampling technique with a total sample of 15 athletes. The research instrument, namely the sit and reach test, measures the level of flexibility. From the results of data processing and analysis using the data normality test and hypothesis testing with the T test formula, that only the squat thrust exercise has an effect on increasing the results of flexibility in karate athletes. These results are seen from the results of data analysis through the calculation of the t test formula with the criteria t count greater than t table (13.510 Ëƒ 1.60) with a confidence level of 0.96 (Î± = 0.05) and the number of samples (N = 15). The findings from this study are that only squat thrust exercises can improve flexibility results. The implementation of the results of this study exercised squat thrust had an effect on increasing the flexibility of the Dojo KKI Karate athletes in South Sumatra.